Sistem Pendukung Keputusan Rekrutmen Karyawan Menggunakan Metode WP PT. Lucky Indah Keramik - Sutan Mohammad Arif; Muhamad Irsan (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
In managing a company, one of the determining factors for a company's success is qualified employees. Selection of human resources is essential to prevent possible adverse impacts on organizational performance. Mistakes in the recruitment process are at risk of harming and threatening business continuity. To get good human resources, an employee selection process is carried out according to the criteria needed from each division. In order to make the employee recruitment process faster and to minimize subjective judgments, we need a system that can produce decisions objectively and quickly. SPK application with the right method can overcome problems in employee recruitment. In this study the authors used the Weighted Product method whereby the selection of criteria and the urgency of the appropriate weight criteria for each division can help make the right decision at PT. Lucky Beautiful Ceramics